214k views
1 vote
Solve SQRT (3x + 1) - 5 = 0.

User Lemur
by
5.0k points

1 Answer

5 votes

√(3x + 1) - 5 = 0

The first step is to collect like terms and that involves moving the constant to one side of the equation. The 5 moves to the right and becomes a positive, (when a negative value crosses to the other side of an equation it becomes a positive and vice versa).

√(3x + 1) = 5

Square both sides (to eliminate the square root sign on the left side of the equation)

3x + 1 = 25

Subtract 1 from both sides of the equation

3x + 1 - 1 = 25 - 1

3x = 24

Divide both sides of the equation by 3

x = 8

(x + 3)^2/3 - 5 = - 1

Add 5 to both sides of the equation

(x + 3)^2/3 - 5 + 5 = - 1 + 5

(x + 3)^2/3 = 4

∛(x + 3)^2 = 4

Find the cube of both sides (to eliminate the cube root sign on the left hand side)

(x + 3)^2 = 4^3

(x + 3)^2 = 64

Add the square root to both sides of the equation to eliminate the square on the left of the equation

x + 3 = √64

x + 3 = 8

Subtract 3 from both sides of the equation

x = 5

User Ammaroff
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.